Relationship Of The Crime Of Embezzlement Of Inheritance Rights In The Family Environment - Andre Sutjahja; Subekti Subekti; Suhartoyo Suhartoyo (Ipso Jure, 2025)
The crime of embezzlement is a criminal act against human property as regulated in the Criminal Code (KUHP). Embezzlement can occur at all levels of society, from lower to upper classes, and often stems from trust that is later broken due to dishonesty. Even within families, a lack of mutual trust can lead to such crimes. This research examines the criminal responsibility of family members who embezzle inherited property. The study uses a normative juridical approach, analyzing secondary legal sources such as laws, books, and encyclopedias. The findings reveal that embezzlement of inherited assets involves unlawfully controlling property or rights that should be distributed among heirs. Inheritance consists of assets left by a deceased person (the heir) for their family (heirs) and must be divided according to legal provisions.  Article 367 of the KUHP categorizes theft within a family as embezzlement when committed by a family member. Meanwhile, Article 376 states that embezzlement within a family is a complaint offense, meaning prosecution can only proceed if the victim files a report. If the report is withdrawn, legal proceedings are halted. Thus, family embezzlement cases often depend on the victim’s decision to pursue legal action.